Beyond Qualifications: Returns to Cognitive and Socio-Emotional Skills in Colombia - Pablo A. Acosta; Noel Muller; Miguel Sarzosa (Institute for the Study of Labor (IZA), 2015)
This paper examines the relationship between individuals' skills and labor market outcomes for the working-age population of Colombia's urban areas. Using a 2012 unique household survey, the paper finds that cognitive skills (aptitudes to perform mental tasks such as comprehension or reasoning) and socio-emotional skills (personality traits and behaviors) matter for favorable labor market outcomes in the Colombian context, although they have distinct roles. Cognitive skills are greatly associated with higher earnings and holding a formal job or a high-qualified occupation. By contrast, socio-emotional skills appear to have little direct influence on these outcomes, but play a stronger role in labor market participation. Both types of skills, especially cognitive skills, are largely associated with pursuing tertiary education. The analysis applies standard econometric techniques as a benchmark and structural estimations to correct for the measurement error of skill constructs.
Keywords: J24; J31; I24; 330; returns to skills; cognitive skills; socio-emotional skills; personality traits; latent skills; unobserved heterogeneity; labor market outcomes; Colombia